The effect of crosswinds on cyclists: An experimental study - Fintelman, D. M.; Sterling, M.; Hemida, H.; Li, F.-X. (Procedia Engineering, 2014)
The aims of this research were to firstly investigate the effect of crosswinds on the aerodynamic behaviour of cyclists and secondly, to determine which parameters (cyclist position and bike type) influenced the aerodynamic forces on cyclists the most. The aerodynamic response of two different full-scale bikes with and without a mannequin has been recorded for a variety of crosswind angles ranging from 0o - 90o (in 15o increments). The results showed that the wind induced force is a function of the crosswind angle. The actual aerodynamic loads arising from such winds can be up to about 2.5 times the aerodynamic drag. It has also been observed that the torso angle has little effect on the lateral force coefficient. In contrast, the bike type significantly affects the aerodynamic forces: at large yaw angles, a road bike is responsible for approximately 60% of the total lateral force coefficient. This study is the first step in the process of determining the effect of crosswind from a full range of angles of attack on cyclists, and will help to improve the safety of cyclists and equipment, and to define guidelines for cycling lanes.